Hak Waris Bagi Ahli Waris yang Tidak Dapat Ditentukan Keberadaannya Menurut Kitab Undang-Undang Hukum Perdata - Anak Agung Krisna Kumala Dewi; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2020)
The heirs whose whereabouts cannot be determined are the heirs who have lost the news, so it is not known whether he is alive or dead. These are usually called missing persons. However, in fact, a lot of heirs ignore the inheritance rights of an heir whose existence cannot be determined. Based on this background, this research was conducted with the aim of elaborating the arrangement of inheritance rights for heirs whose existence cannot be determined and the legal consequences for heirs whose existence is known after the inheritance is divided. This study used a normative legal research method with a statutory and conceptual approach. The results of this study showed that the existence of inheritance rights for heirs that cannot be determined is regulated in Article 463 of the Civil Code. The inheritance rights of heirs whose existence cannot be determined remain attached to it in accordance with the provisions of Article 467 of the Civil Code. However, as long as the whereabouts of the heir are not known, the position will be replaced by the successor heirs. Furthermore, as a legal consequence after an heir is known to exist, the replacement heir is obliged to return all the inherited assets received under the provisions of Article 482 paragraph (1) of the Civil Code.